2021
DOI: 10.1530/ec-20-0473
|View full text |Cite
|
Sign up to set email alerts
|

The use of prednisolone versus dual-release hydrocortisone in the treatment of hypoadrenalism

Abstract: The introduction of adrenocortical extract in 1930, improved life expectancy to between two and five years with further increases seen with the introduction of cortisone acetate from 1948. Most patients are now treated with synthetic hydrocortisone, and incremental advances have been made with optimisation of daily dosing and the introduction of multi-dose regimens. Today there remains a significant mortality gap between individuals with treated hypoadrenalism and the general population. It is unclear whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Evidence from 2 randomized-controlled trials (RCTs) has shown a reduction in CV disease risk parameters with modified release hydrocortisone compared to conventional therapy [9]. Though Plenadren® carries a significantly higher cost basis to the other traditional therapeutic glucocorticoid medications and carries a higher vulnerability to malabsorption during intercurrent gastrointestinal illness [16].…”
Section: Novel Glucocorticoid Replacement Therapiesmentioning
confidence: 99%
“…Evidence from 2 randomized-controlled trials (RCTs) has shown a reduction in CV disease risk parameters with modified release hydrocortisone compared to conventional therapy [9]. Though Plenadren® carries a significantly higher cost basis to the other traditional therapeutic glucocorticoid medications and carries a higher vulnerability to malabsorption during intercurrent gastrointestinal illness [16].…”
Section: Novel Glucocorticoid Replacement Therapiesmentioning
confidence: 99%
“…The mRNA level further found to be positively correlated with insulin amount, and PER3 and CRY2 expression negatively correlat-ed with the glycated haemoglobin in blood. Noticeably, BMAL1, PER3, PPARD, and CRY2 genes expression were found to be altered in women with gestational diabetes as compared to the pregnant normoglycemic women [31].…”
Section: Diurnal Rhythms and Glucose Metabolism In Livermentioning
confidence: 91%
“…The synthetic corticosteroids, prednisone, and prednisolone have longer half-lives than hydrocortisone. Indeed, prednisolone has the same blood profile as Plenadren [20 ▪ ], but it is readily available as an inexpensive generic. Because they are not the ‘physiologic’ glucocorticoid, prednisone and prednisolone are not favored for treating CAH [1], especially in children.…”
Section: Alternative Hydrocortisone Preparationsmentioning
confidence: 99%